2022
DOI: 10.1111/fare.12802
|View full text |Cite
|
Sign up to set email alerts
|

Is helicopter parenting related to college students’ mental health? A typological and cross‐cultural approach

Abstract: ObjectiveThe goal of this study is to uncover latent classes of maternal and paternal helicopter parenting among American and Chinese college students, and to examine whether latent classes of maternal and paternal helicopter parenting are related to college students’ mental health (depression and self‐esteem).BackgroundPrevious studies have examined the association between helicopter parenting and college students’ well‐being. However, less is known about how the multidimensional construct of helicopter paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Our study showed low mean scores of helicopter parenting style among our sample, and a lack of association with the medical trainees’ mental health outcomes. This might be related to cultural context, however, literature shows larger detrimental effects of helicopter parenting in collectivist cultures than in individualistic cultures [ 66 , 67 ]. In collectivist cultures, like the context of our study, university students do not work and depend on their parents financially during their university education.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed low mean scores of helicopter parenting style among our sample, and a lack of association with the medical trainees’ mental health outcomes. This might be related to cultural context, however, literature shows larger detrimental effects of helicopter parenting in collectivist cultures than in individualistic cultures [ 66 , 67 ]. In collectivist cultures, like the context of our study, university students do not work and depend on their parents financially during their university education.…”
Section: Discussionmentioning
confidence: 99%